2012
DOI: 10.1038/nature10781
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to stability and change in intelligence from childhood to old age

Abstract: Understanding the determinants of healthy mental ageing is a priority for society today. So far, we know that intelligence differences show high stability from childhood to old age and there are estimates of the genetic contribution to intelligence at different ages. However, attempts to discover whether genetic causes contribute to differences in cognitive ageing have been relatively uninformative. Here we provide an estimate of the genetic and environmental contributions to stability and change in intelligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
198
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(210 citation statements)
references
References 27 publications
9
198
2
1
Order By: Relevance
“…13 New analytical tools have also recently been developed that rely on direct measures of genetic relatedness, and thus do not rely on the EEA, to estimate heritability [63][64][65]. 14 For a more detailed discussion of the concept of heritability, see Hatemi et al [26]. 15 Center for Responsive Politics, https://www.opensecrets.org/.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 New analytical tools have also recently been developed that rely on direct measures of genetic relatedness, and thus do not rely on the EEA, to estimate heritability [63][64][65]. 14 For a more detailed discussion of the concept of heritability, see Hatemi et al [26]. 15 Center for Responsive Politics, https://www.opensecrets.org/.…”
Section: Resultsmentioning
confidence: 99%
“…As a field, behaviour genetics represents an impressive collection of findings on the influence of genetic variation on a large range of behaviours, including: altruism [9], entrepreneurism [10], financial risk taking [9,11], impulsivity [12], intelligence [13,14], leadership [15][16][17], non-rational decision-making [18], smoking addiction [19], socioeconomic status [20] and trust [21]. Indeed, so widespread are findings of heritable behaviour that one scholar has coined the 'first law' of behaviour genetics: 'All human behavioural traits are heritable' [22].…”
Section: Theoretical and Empirical Evidencementioning
confidence: 99%
“…First, variation in genetic architecture has been associated with the intelligence quotient (IQ) distribution itself. Although IQ overall is highly heritable (21)(22)(23)(24), there is evidence that severe intellectual disabilities, which exist at the low tail of the Significance Autism spectrum disorder (ASD) research is complicated by heterogeneity. There are several types of genetic risk factors for ASDs, and that diversity may be reflected in case presentation.…”
Section: Identifying Variables That Index Differences In Genetic Archmentioning
confidence: 99%
“…Paradoxically, even though GCA is highly vulnerable to the influence of aging, there is a remarkable stability in individuals' GCA relative to their same-age peers (10,11). It has even been shown that childhood GCA can account for GCA-cortical thickness associations in old age (12).…”
mentioning
confidence: 99%